KONSTRUKSI SOSIAL HAMBATAN IMPLEMENTASI PERAN SERTA MASYARAKAT DALAM PENYELENGGARAAN JAMINAN HALAL PANGAN LOKAL DAN PERLINDUNGAN KONSUMEN: PENELITIAN SOSIAL LEGAL TERHADAP INOVASI MAKANAN HALAL DI PROVINSI BANTEN - Ikomatussuniah, Ikomatussuniah; Sariyah, Sariyah (International Journal Mathla’ul Anwar of Halal Issues, 2023)
The community's participation in the implementation of halal product assurance regulates in Articles 53, 54, and 55 of the JPH Law. However, its fact is under expectations. This paper aims to determine the obstacles in implementing the community's participation in local halal food assurance based on halal product assurance regulations in Banten province and the efforts made by the government to protect Muslim consumers. The study used socio-legal research methods with an abductive approach and qualitative data analysis, then data collection done by using in-depth interviews and related legal materials. The results showed the existence of four obstacles in the implementation of community participation in local halal food assurance based on halal product assurance regulations in Banten province, namely, the willingness to obtain halal raw materials for local food is limited, the processing process of local food products is less professional, the packaging of local food products is less attractive, the sale of halal local food products is still traditional and less desirable and weak public knowledge of consumer rights. The tripartite government efforts are essential to collaborate, namely the government (BPJPH), civil society, and business actors.